(untitled) (Andamios, Revista de Investigación Social, 2014)
The topic of the “electoral proportionality, closely linked to the” proportional representation”, has been rarely discussed in Mexican academia. While at the court has been discussed extensively since 1998, and apparently closed in september 2009, is still disagreement about the training of law in connection with the interpretation of the constitutional provision in that area. The disagreement among federal courts reveals a dark area of legal and impacts the design of mainly local legal standards for the allocation of legislative seats by proportional representation.